Advance in ultrasonic spray pyrolysis (USP) for the synthesis of gold nanoparticles - Stopić, Srećko R.; Fridrih, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: Ultrasonic spray pyrolysis (USP) is usually used for the preparation of submicronic and nanosized gold powders. This is a simple method for a synthesis from an aerosol containing dissolved metallic salts such as gold chloride, gold nitrate, and gold-acetate, obtained in the ultrasonic field using frequencies ranging from 0.8 to 2.5 MHz. Methods: The USP method combines aerosol formation in an ultrasonic field, transport of an aerosol with a carrier gas to the reactor and final reduction of HAuCl4 with a used gas such as hydrogen and carbon monoxide. The thermal decomposition of gold acetate takes place in a neutral atmosphere such as nitrogen and argon at elevated temperatures. The chemical reduction of HAuCl4 takes place in the aqueous phase using sodium citrate and sodium boride after heating water solution. Results: Powders of gold were obtained at room temperature using hydrogen reduction in an ultrasonic field at room temperature from HAuCl4 using a frequency of 0.8 MHz. The obtained gold particles were analysed using scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS). The formed particles are round and agglomerated. An increase in temperature to 260°C and 500°C leads to the formation of spherical and cylindrical gold particles. Conclusion: New improved equipment for an ultrasonic spray pyrolysis synthesis of gold powder from HAuCl4 with hydrogen reduction was offered by PRIZMA, Kragujevac, Serbia, enabling a controlled reduction process with better prevention of piezo transducers in an ultrasonic field and increased aerosol production and its transport to the reaction furnace.